2002
DOI: 10.1034/j.1600-0455.2002.430211.x
|View full text |Cite
|
Sign up to set email alerts
|

HRCT findings in the lungs of primary care patients with lower respiratory tract infection

Abstract: HRCT is more sensitive than chest radiography in detecting LRTI-related lung lesions in a primary care population. The pattern typically comprises subtle scattered polymorphous opacities with varying attenuation affecting several lung segments. LRTI-related HRCT pattern deserves consideration as a differential diagnostic alternative in patients examined due to any lower respiratory tract symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Van Gageldonk-Lafeber et al observed no association between detected bacterial and viral pathogens and either diagnosis made by general practitioners or subject's reported symptoms ( 40 ). Moreover, physical examination alone was shown to have a sensitivity of 50–70% and specificity of 60–75% as well as a negative predictive value of 60% and a positive predictive value of 50% ( 41 , 42 ). The difficulty in establishing an etiologic outpatient diagnosis in acute febrile respiratory illness stems from overlap in symptoms and signs, limitations of available diagnostic tests, and the time lag in receiving results from laboratory tests.…”
Section: Discussionmentioning
confidence: 98%
“…Van Gageldonk-Lafeber et al observed no association between detected bacterial and viral pathogens and either diagnosis made by general practitioners or subject's reported symptoms ( 40 ). Moreover, physical examination alone was shown to have a sensitivity of 50–70% and specificity of 60–75% as well as a negative predictive value of 60% and a positive predictive value of 50% ( 41 , 42 ). The difficulty in establishing an etiologic outpatient diagnosis in acute febrile respiratory illness stems from overlap in symptoms and signs, limitations of available diagnostic tests, and the time lag in receiving results from laboratory tests.…”
Section: Discussionmentioning
confidence: 98%
“…We think that the definition of asymptomatic infection should be reserved to the culture or PCR-positive patients without symptoms who have either seroconversion of antibodies or any lung infiltrate at thorax HRCT consistent with pneumonia-since it has been reported that HRCT has greater sensitivity than Chest X-Ray in diagnosing pneumonia [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…3 There are several studies that reported the superiority of CT to chest radiography for detecting pneumonia. [4][5][6][7][8][9] Although CT is more sensitive in diagnosing pneumonia and may be more specific for certain pathogens than chest radiography, objective guidelines regarding its indication are lacking. 10 Furthermore, whether CT improves the prognosis of pneumonia patients has not been revealed.…”
Section: Introductionmentioning
confidence: 99%